Methodology of designing quality into manufacturing process and equipment: A proposal - Muhammad Iqbal, Muhammad Hussain, Dr.; Zuraidah, Mohd Zain, Prof. Dr. (2012)
Many manufacturing organizations are unable to achieve acceptable quality performance because they do not have total control over their processes and equipment. Strict inspection cannot guarantee a stable supply of quality products; instead, there is a need to design quality into manufacturing processes and equipments. Quality control techniques are usually studied and implemented in isolation of the manufacturing process and equipment, therefore failing to give optimum results. It is a far better strategy to integrate the critical control functions of quality, production, inventory, and process control. Taking this into account, a 3-year research project is proposed. The aim is to develop a methodology that integrates the critical control functions of the process. In developing this methodology, methodical questions such as ‘how should the manufacturing process be analyzed in the light of relevant quality parameters?’, ‘how should the equipment be analyzed?’, ‘how should quality tools be selected to eliminate waste and guarantee quality at the processing points?’ will be asked. The project makes use of a case study approach, where an existing manufacturing facility is put to test. This paper outlines the proposed work. It defines the scope of the study, the research mode, the choice of investigative questions to be asked, the selection of the manufacturing facility to be used as the test subject, and other pertinent research parameters.